The birth of a borough an archaeological study of Anglo-Saxon Stafford - Carver, Martin Oswald Hugh 1941- (Boydell Press, 2010)
The majority of our county towns, and the shires themselves, owe their origins to the campaigns of Alfred and his children Edward the Elder and Aethelflaeda, Lady of the Mercians, in the late 9th and early 10th centuries. Stafford is one such town, and the large-scale archaeological examinations undertaken there over the last fifty years have provided an extraordinary, unique opportunity to piece together the history of such a 'typical' town. A centre for the delivery of grain tribute during the Dark Ages, it was commandeered in the tenth century by Aethelflaeda in order to construct a burh there. This new foundation was a fort, provided with a 'vicus' in which the centralised production of Roman-style pottery ('Stafford Ware') was undertaken and supplied to the chain of west midlands burhs. The case of Stafford has prompted a new review of the origins of county towns as a whole, and the composition of a new model for the birth of the Anglo-Saxon borough on which the local administration of England has ever since been based